Driving cycle development methods: case study in Malaysia - Nurru Anida Ibrahim; Siti Norbakyah Jabar; Arunkumar Subramaniam; Wan Nural Jawahir Wan Yussof; Salisa Abdul Rahman (Universitas Ahmad Dahlan, 2023)
Over the years, many models have been created to estimate pollution inventories and fuel usage. These models can be divided into two types: travel-based and fuel-based. One of the most used travel-based models for estimating emission inventories is driving cycles. It can be used for a variety of different things, such as establishing pollution regulations, traffic control, and calculating journey time. For these goals, researchers have previously attempted to use easily available, well-established driving cycles. In many ways, however, the local environment differs greatly from that of the driving cycle’s genesis. As a result, these cycles’ applications have failed to provide high-quality results. This research aims to analyse the various approaches utilised for driving cycle construction in various locations of Malaysia under varied operational situations.